2020
DOI: 10.6007/ijarafms/v10-i1/6993
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Leadership on Employee Innovative Work Behaviour in Facilities Management Service Providers in Oman

Abstract: Employee innovative work behavior (EIWB) within organizations plays a key role in achieving the goals of the organization. The current study describes the level of employee innovative work behavior among Facility Management (FM) service providers in Oman and the effect of leadership on employee innovative work behavior before then after an employee motivation has been included as mediator. It focuses on mid-level managers, technicians and supervisors of FM service providers in Oman. Self-structured questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
1
0
2
Order By: Relevance
“…Leadership Factor: There are various leadership styles have been studied on IWB such as Transformational leadership, Transactional leadership and Laisser-Faire leadership (Alheet et al, 2021;Khan et al, 2020;Afsar & Umrani, 2020;Bawuro et al, 2018;Chatchawan et al, 2017;Gashema, 2021;Grošelj et al, 2020;Sinaga et al, 2021;Tan et al, 2021) Ethical Leadership (Wen et al, 2021;Hashim, 2021) Inclusive Leadership (Alshoukri et al, 2020;Javed et al, 2020;Bannay et al, 2020;Javed et al, 2019) Entrepreneurial Leadership (Li et al, 2020) and Servant Leadership (Cai et al, 2018). According to a recent systematic literature review by AlEssa & Durugbo, (2021) and El Alfy & Naithani, (2021) found that leadership studies dominate research related to IWB and transformational leadership (TL) is the most studied style of leadership linked to IWB.…”
Section: Messmann and Mulder (2012)mentioning
confidence: 99%
See 1 more Smart Citation
“…Leadership Factor: There are various leadership styles have been studied on IWB such as Transformational leadership, Transactional leadership and Laisser-Faire leadership (Alheet et al, 2021;Khan et al, 2020;Afsar & Umrani, 2020;Bawuro et al, 2018;Chatchawan et al, 2017;Gashema, 2021;Grošelj et al, 2020;Sinaga et al, 2021;Tan et al, 2021) Ethical Leadership (Wen et al, 2021;Hashim, 2021) Inclusive Leadership (Alshoukri et al, 2020;Javed et al, 2020;Bannay et al, 2020;Javed et al, 2019) Entrepreneurial Leadership (Li et al, 2020) and Servant Leadership (Cai et al, 2018). According to a recent systematic literature review by AlEssa & Durugbo, (2021) and El Alfy & Naithani, (2021) found that leadership studies dominate research related to IWB and transformational leadership (TL) is the most studied style of leadership linked to IWB.…”
Section: Messmann and Mulder (2012)mentioning
confidence: 99%
“…Transformational leadership (Alheet et al, 2021;Khan et al, 2020;Afsar & Umrani, 2020;Bawuro et al, 2018;Gashema, 2021;Grošelj et al, 2020;Sinaga et al, 2021;Tan et al, 2021) (Afsar & Masood, 2018;Alnajjar & Hashim, 2020;Alshahrani et al, 2023;Arsawan et al, 2022;Bednall et al, 2018;Bin Saeed et al, 2019;Bin Saripin & Kassim, 2019;Contreras et al, 2020;Ferdinan & Lindawati, 2021;Grošelj et al, 2021;Hansen & Pihl-Thingvad, 2019;Khan et al, 2019;Sukumarl Koednok, 2023;Rahmah et al, 2020;Stanescu et al, 2020;Sudibjo & Prameswari, 2021;Tan et al, 2021;) Transactional Leadership (Alheet et al, 2021;Contreras et al, 2020;Faraz et al, 2018;Hansen & Pihl-Thingvad, 2019;Kustanto et al, 2020;Rahmah et al, 2020) Ethical Leadership (Hashim, 2021;Musenze & Mayende, 2022;Wen et al, 2021) Inclusive Leadership (Bannay et al, 2020), (Alshoukri et al, 2020;ASLAN, 2019;Javed et al, 2019Javed et al, , 2020…”
Section: Leadershipunclassified
“…Penelitian ini mendukung hasil penelitian sebelumnya yang dilakukan oleh Alshoukri et al (2020) yang menyatakan inklusivitas pemimpin diarahkan mendorong dan menghargai sudut pandang yang berbeda dari anggota yang beragam dalam interaksi kelompok. Karyawan yang didukung oleh pemimpin mereka akan mendapat lebih banyak kebebasan untuk terlibat dalam perilaku inovatif.…”
Section: Tabel 5 Hasil Analisis Jalurunclassified
“…mendorong dan menghargai cara berpikir yang berbeda dari anggota organisasi (Alshoukri et al, 2020) Pemimpin yang inklusif mampu menyediakan sumber daya informasi, waktu dan dukungan yang diperlukan dalam membentuk perilaku inovatif karyawan. Pemberdayaan kepemimpinan inklusif berfokus dalam hal memimpin, berbagi kekuatan, pembelajaran serta pelatihan, dimana pemimpin akan menempatkan dirinya ke dalam cara pandang orang lain dan menghargai cara berpikir yang berbeda dari anggota organisasi.…”
unclassified
“…The extant literature on inclusive leadership and safety behaviour show studies have been conducted in many countries outside of Indonesia (Choi et al ., 2017; Jing et al ., 2018; Qi et al ., 2019; Ye et al ., 2019; Alshoukri et al ., 2020). We argue this is a research gap that our study can address.…”
Section: Introductionmentioning
confidence: 99%